1994
DOI: 10.1111/j.1476-5381.1994.tb13208.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous vasodilatation induced by nitric oxide‐evoked stimulation of afferent nerves in the rat

Abstract: 1 The site of action at which nitric oxide (NO) may contribute to neurogenic vasodilatation in the hindpaw skin of urethane-anaesthetized rats was examined by the use of N0-nitro-L-arginine methyl ester (L-NAME), an inhibitor of NO synthase. 2 Skin blood flow was measured by laser Doppler flowmetry, and neurogenic vasodilatation was evoked either by topical application of mustard oil (5%) or antidromic electrical stimulation of the saphenous nerve (antidromic vasodilatation).3 L-NAME (60 lmol kg-', i.v.) atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1
1

Year Published

1994
1994
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 32 publications
2
24
1
1
Order By: Relevance
“…In vivo experiments using a rat model of endotoxicosis have shown that the early hypotension and the loss of vascular responsiveness to noradrenaline occurring within the first 1 h of shock was dependent on NO production and apparently involved the activation of cNOS in either endothelial or neural cells (Wright et al, 1992;Szabo et al, 1993). Some studies have shown that NO appears to increase CGRP release from perivascular nerves in cerebral arteries (Wei et al, 1992), and microvessels in skin (Holzer & Jocic, 1994;Hughes & Brain, 1994;Kajekar et al, 1995) by observation of blood flow in response to a CGRP receptor blocker. On the other hand, several studies have indicated that CGRP does not account for vasodilatation in response to NO (Ralevic et al, 1992;Ayajiki et al, 1994;Faraci & Breese, 1994;Brian et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…In vivo experiments using a rat model of endotoxicosis have shown that the early hypotension and the loss of vascular responsiveness to noradrenaline occurring within the first 1 h of shock was dependent on NO production and apparently involved the activation of cNOS in either endothelial or neural cells (Wright et al, 1992;Szabo et al, 1993). Some studies have shown that NO appears to increase CGRP release from perivascular nerves in cerebral arteries (Wei et al, 1992), and microvessels in skin (Holzer & Jocic, 1994;Hughes & Brain, 1994;Kajekar et al, 1995) by observation of blood flow in response to a CGRP receptor blocker. On the other hand, several studies have indicated that CGRP does not account for vasodilatation in response to NO (Ralevic et al, 1992;Ayajiki et al, 1994;Faraci & Breese, 1994;Brian et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…In the skin, the vasodilator response induced by axon reflexes or antidromic electrical stimulation seems to be mediated mostly by CGRP (Brain and Williams, 1989;Holzer, 1992). NO is unlikely to be involved in the rat skin microvasculature since NOS inhibitors do not affect the response (Ralevic et al, 1992;Holzer and Jocic, 1994). It is suggested that release of NO is involved in edema formation in rat paw skin induced by electrical stimulation of the saphenous nerve, but the vasodilator action of NO is unimportant in this context (Kajekar et al, 1995).…”
Section: Acupuncture Axon Reflex and Neurogenic Inflammationmentioning
confidence: 99%
“…Together with the observation that the CGRP8-37-sensitive component of the vasodilator response to SNP is abolished by capsaicin-induced defunctionalization of afferent, neurones (Holzer & Jocic, 1994), this finding provides strong evidence that part of the SNP-evoked rise in cutaneous blood flow is due to release of CGRP from afferent nerves fibres. A similar conclusion holds true for the ability of SNP to dilate cerebral arterioles in the cat (Wei et al, 1992).…”
Section: Discussionmentioning
confidence: 67%
“…Effect of L-NAME and methylene blue on the cutaneous hyperaemia induced by SNP The inhibitor of NO synthase, N0-nitro-L-arginine methyl ester (L-NAME, 15 mg kg-l; Holzer & Jocic, 1994), or its vehicle (saline, 1 ml kg-') was injected i.v. 15 min before the third intraplantar application of SNP (150 pmol).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation